Malay secret societies in the northern Malay states, 1821-1940s - Mahani Musa (Monographs of the Malaysian Branch, Royal Asiatic Society)
This important study describes the origins and development of Malay secret societies in the northern states of the Malay peninsula between 1821 and 1941. The author focuses on the activities of several organizations, including the Red Flags and White Flags in Penang, Perak and Kedah. These societies had their beginnings as welfare and religious associations, but often degenerated into criminal activities. Their involvement often led to disturbances at Boria musical performances, the Muharam celebrations and soccer matches.